Stress fracture prevalence in elite figure skaters - Dubravcic-Simunjak, S.; Kuipers, H.; Moran, J.; Pecina, M.; Simunjak, B.; Ambartsumov, R.; Sakai, H.; Mitchel, D.; Shobe, J. (Journal of Sports Science & Medicine, 2008)
In conclusion the data suggest that the cumulative risk of stress fractures is high in figure skating, especially among single figure skaters and female pair skaters. In the light of increasing physiological demands from rigorous training and competitive schedules throughout the skating season, prevention deserves more emphasis. Proper education to athletes and coaches about training regimes, together with early recognition of stress fracture symptoms may help to decrease the stress fracture risks. Because of the large number of competitions and shows in a short period of time, it is recommended to critically review the competitive schedule. In addition, rule changes concerning the ages and skaters possibilities to compete in both senior and junior events may have to be considered.